ANALISA DAMPAK FAKTOR MAKRO EKONOMI : INFLASI DAN KURS PADA DUA ERA PEMERINTAHAN TERHADAP NILAI PROFITABILITAS PERUSAHAAN PERBANKAN SYARIAH ( Studi pada Bank Umum Syariah Periode 2009 - 2018 ) - Natalina, Sri Anugrah; Zuraidah, Zuraidah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2021)
Banking is a type of service business that is very vulnerable to be influenced by many factors, both internal and external. The dominating external factors are those related to government regulations, for example: the SBI interest rate, exchange rate, fiscal policy and the inflation rate. The level of profitability of a Sharia Commercial Bank (BUS) contained in the annual report of a BUS may not be used as a factor to be able to reveal the size of the profitability (ROA) which can be influenced by external factors. This shows that during the SBY administration era, inflation had no effect on the level of profitability of BUS. This may be due to the inflation rate that occurs with a more stable value, namely the conversion rate at 3-5. However, if the inflation rate fluctuates, it can have an influence on profitability in BUS. In the era of Jokowi's administration, it was shown that in the early years of his administration, namely 2014-2015, it showed a high inflation rate so that this may have resulted in an influence on the profitability of BUS. the two variables, namely inflation and exchange rate have an influence on the profitability of BUS. And in the Jokowi era, the influence has increased by 10% compared to the SBY era. In the SBY era, it only contributed 20.5%, while in the Jokowi era it was 30.5%. Other variables outside this study that can affect BUS profitability / ROA can be derived from SBI and GDP.